Accounting and Financial System Reform in a Transition Economy: A Case Study of Russia - McGee, Robert W. (Springer US : Imprint: Springer, 2005)
Much has been written about the economic and political problems of countries that are in the process of changing from centrally planned systems to market systems. Most studies have focused on the economic, legal, political and sociological problems these economies have had to face during the transition period. However, not much has been written about the dramatic changes that have to be made to the accounting and financial system of a transition economy. This book was written to help fill that gap. Using Russia as a case study the authors examined all the major aspects of accounting reform, starting with problems of implementation. They also examined the current state of auditing in Russia. Other studies looked at the changes in accounting education that are sweeping through Russian universities and the private sector and how international accounting certification is being used to meet the demand for credible accounting practitioners. They also devote chapters to corporate governance issues, the Russian tax system and the problems Russian enterprises face when they try to attract foreign direct investment. "Accounting and Financial System Reform in a Transition Economy: A Case Study of Russia" is the first in a series on accounting and financial system reform in transition and developing economies. Other volumes will examine accounting and financial system reform in Eastern Europe and Asia and the changes to the taxation and public finance systems these countries are going through in their transition to market economies.